Influencers’ Impact on Moral Degradation of Betawi Generation Alpha in Shaping Pancasila Character Values - Anastya Basyith Ad Dauwi; Evi Dalilah; Ella Yanova; Mercynda Putri; Yohamintin Yohamintin (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the impact of social media influencers on the moral degradation of Betawi Generation Alpha and its implications for shaping character based on Pancasila values. Methodology: This research employed a qualitative design using a phenomenological approach. Data were collected through in-depth interviews, classroom and social observations, and documentation. Informants consisted of five Generation Alpha children, two teachers, two parents, and two community leaders selected through purposive and snowball sampling techniques. Data analysis followed the interactive model proposed by Miles and Huberman. Main Findings: The findings reveal that social media influencers exert a substantial influence on the character development of Betawi Generation Alpha. Early exposure to digital technology, intensive social media use, and limited parental supervision position influencers as prominent role models in children’s daily lives. Consequently, there is a noticeable decline in religious commitment, moral and ethical conduct, responsibility, national (Pancasila) values, and Betawi socio-cultural identity, as reflected in changes in behavior, language patterns, discipline, and cultural awareness. Novelty/Originality of This Study:This study contributes novel insights by contextualizing the influence of social media influencers within Betawi local culture and Pancasila-based character education. It highlights the interaction between digital exposure, moral internalization failure, and the erosion of local cultural values, offering an integrated perspective that enriches current discussions on character education in the digital era.